MODELLING OF VESSEL TRAFFIC ON THE CANAL NETWORK DANUBE-TISA-DANUBE - BACKALIC, Todor (Doprava a spoje, 2012)
Simulation model that enables the examination of vessel traffic process at different traffic densities. Obtained results may be used as a planning and decision-making support in the process of vessel traffic control in ship lock area and the part of navigable canals.